Citizen innovation: Exploring the responsibility governance and cooperative mode of a "post-Schumpeter" paradigm - Jin Chen; Linghui Han; Guannan Qu (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
It has become a burgeoning trend for the innovation paradigm to shift fromproducer-dominant to non-producer centric. Based on a critical review of the non-producer innovationliterature, we identified several limitations of existing non-producer innovation paradigms-grassrootsinnovation, free innovation, common innovation, and social innovation-along two critical dimensions:responsibility governance of innovation outcomes and effective organizing form for collaborativeinnovation. To address the theoretical gaps in existing non-producer innovation research, we proposecitizen innovation (CI) as a new integrated innovation paradigm to balance these two dimensions byfocusing on citizens' unique role as innovators. In the paper, we discuss CI's theoretical frameworkfrom three aspects: (1) citizen participation in innovation; (2) open collaborative innovation as theorganizing form; (3) the process and incentive mechanisms of citizen innovation. We also offer tworeal-world examples to support the main propositions and mechanisms of CI. To conclude, we reflecton the limitations of the current research and discuss future directions for CI research.
Keywords: 650; citizen innovation; innovation paradigm; non-producer innovation; open collaboration